Treatment of a Refractory Skin Ulcer Using Punch Graft and Autologous Platelet-Rich Plasma - Mauro Carducci; Marcella Bozzetti; Marco Spezia; Giorgio Ripamonti; Giuseppe Saglietti (Hindawi Limited, 2016)
Background. Chronic ulceration of the lower legs is a relatively common condition amongst adults: one that causes pain and social distress and results in considerable healthcare and personal costs. The technique of punch grafting offers an alternative approach to the treatment of ulcers of the lower limbs. Objective. Combining platelet-rich plasma and skin graft enhances the efficacy of treating chronic diabetic wounds by enhancing healing rate and decreasing recurrence rate. Platelet-rich plasma could, by stimulating dermal regeneration, increase the take rate after skin grafting or speed up reepithelialization. Methods and Materials. The ulcer was prepared by removing fibrin with a curette and the edges of the ulcer were freshened. The platelet-rich plasma has been infiltrated on the bottom and edges of the ulcer. The punch grafts were placed in 5 mm holes arranged. The ulcer was medicated with hydrogel and a pressure dressing was removed after 8 days. Results. After a few days the patient did not report more pain. Granulation tissue appeared quickly between implants. Most of the grafts were viable in 2-3 weeks. The grafts gradually came together to close the ulcer and were completed in four months.